TRACK POSITION TRAINS – A NEW INFORMATION SUPPORT FOR STATION DISPATCHERS (Perner's Contacts, 2019)
Operational management of rail transport requires high-quality information support. All operational decisions are linked to information that is available to all competent persons and can work for them. The paper represents a new application in the conditions of the Infrastructure Manager (ŽSR), which is primarily intended for station dispatchers. Nowadays, they have overview only on their station and adjacent intersections. The prepared application allows you to get an overview not only in the vicinity of your own station but also in the selected route sections at the discretion of each user.
Keywords: the train position; dispatcher apparatus; operational management